Heroes of the frontier : a novel - Eggers, Dave (New York : Vintage Books, 2017)
Josie and her husband have split up, she's been sued by a former patient and lost her dental practice, and she's grieving the death of a young man senselessly killed. When her ex asks to take the children to meet his new fiancée's family, Josie makes a run for it, figuring Alaska is about as far as she can get without a passport. Josie and her kids, Paul and Ana, rent a rattling old RV named the Chateau, and at first their trip feels like a vacation; they see bears and bison, they eat hot dogs cooked on a bonfire, and they spend nights parked along icy cold rivers in dark forests. But as they drive, pushed north by the ubiquitous wildfires, Josie is chased by enemies both real and imagined. Past mistakes pursue her tiny family to the very edge of civilization.
Keywords: Single parents -- Fiction; Domestic fiction